From the Enlightenment to Black Lives Matter tracing the impacts of racial trauma in Black communities from the colonial era to the present - Waldron, Ingrid (Emerald Publishing, 2025)
A timely challenge to the colonial and imperial legacy of psychiatry, From the Enlightenment to Black Lives Matterdemonstrates how the politics of race and psychiatric diagnosis collide when diagnosing Black people and what this means for our current public health crisis
Keywords: Rassismus; Psychiatrische Untersuchung; Schwarze; Black people / Mental health / Canada; Psychiatry / Social aspects / Canada; Racism in medicine / Canada